Thermal Spray Processes in Concentrating Solar Power Technology - Felice Rubino; Pedro Poza; Germana Pasquino; Pierpaolo Carlone (Metals, 2021)
Solar power is a sustainable and affordable source of energy, and has gained interest from academies, companies, and government institutions as a potential and efficient alternative for next-generation energy production. To promote the penetration of solar power in the energy market, solar-generated electricity needs to be cost-competitive with fossil fuels and other renewables. Development of new materials for solar absorbers able to collect a higher fraction of solar radiation and work at higher temperatures, together with improved design of thermal energy storage systems and components, have been addressed as strategies for increasing the efficiency of solar power plants, offering dispatchable energy and adapting the electricity production to the curve demand. Manufacturing of concentrating solar power components greatly affects their performance and durability and, thus, the global efficiency of solar power plants. The development of viable, sustainable, and efficient manufacturing procedures and processes became key aspects within the breakthrough strategies of solar power technologies. This paper provides an outlook on the application of thermal spray processes to produce selective solar absorbing coatings in solar tower receivers and high-temperature protective barriers as strategies to mitigate the corrosion of concentrating solar power and thermal energy storage components when exposed to aggressive media during service life.